Cost‐effectiveness of treating vascular leg ulcers with UrgoStart® and UrgoCell® Contact. Issue 1 (21st February 2014) - Augustin, Matthias; Herberger, Katharina; Kroeger, Knut; Muenter, Karl C.; Goepel, Lisa; Rychlik, Reinhard
Abstract: Although chronic wounds have a high socio‐economic impact, data on comparative effectiveness of treatments are rare. UrgoStart ® is a hydroactive dressing containing a nano‐oligosaccharide factor (NOSF). This study aimed at evaluating the cost‐effectiveness of this NOSF‐containing wound dressing in vascular leg ulcers compared with a similar neutral foam dressing (UrgoCell ® Contact) without NOSF. Cost‐effectiveness analysis from the perspective of the German statutory health care system was performed using a decision tree model for a period of 8 weeks. Cost and outcome data were derived from the clinical study 'Challenge' suggesting a response rate (≥40% wound size reduction) of UrgoStart ® of 65·6% versus 39·4% for the comparator. In the treatment model, effect‐adjusted costs of €849·86 were generated after 8 weeks for treatment with UrgoStart ® versus €1335·51 for the comparator resulting in an effect‐adjusted cost advantage of €485·64 for UrgoStart ® . In linear sensitivity analyses, the outcomes were stable for varying assumptions on prices and response rates. In an 8‐week period of treatment for vascular leg ulcers, UrgoStart ® shows superior cost‐effectiveness when compared with the similar neutral foam dressing without any active component (NOSF). As demonstrated within a randomised, double‐blind clinical trial, UrgoStart ® is also more effective in wound area reduction than the neutral foam dressing. Wound healing was not addressed in this clinical trial. Follow‐up data of 12 months to allow for reulceration assessment were not generated.